Stabilization of Crossflow Instability with Plasma Actuators: Linearized Navier Stokes Simulations - Kang,KL; Ashworth,R; Mughal,MS (2017)
This paper describes work carried out within the Buterfli project to look at the control of transition causing “target” cross flow vortices through the generation of subdominant “killer” modes with distributed plasma actuation leading to non-linear interaction and damping of the “target” modes. Experimental studies performed at the TsAGI T124 tunnel for a swept plate subject to favourable pressure gradient flow have been compared with numerical modelling. A mathematical model for the actuator developed at TsAGI has been implemented in a linearised Navier Stokes solver and used to predict “killer” mode amplitudes at a measurement plane in the experiment. This shows good agreement with experiment and is used as input for non-linear PSE analysis to predict the effect of these modes on transition. Whilst the numerical model indicates a delay in transition in the experiment actuator induced unsteadiness results in the generation of travelling cross flow modes and an advance rather than delay in transition